Diameter-dependent in vitro performance of biodegradable pure zinc wires for suture application. Issue 8 (August 2019) - Guo, H.; Cao, R.H.; Zheng, Y.F.; Bai, J.; Xue, F.; Chu, C.L.
Abstract: In this study, biodegradable pure zinc wires with 3.0 mm and 0.3 mm in diameter were prepared via hot-extrusion and subsequent cold-drawing process respectively. The microstructure, mechanical performance, corrosion behavior, in vitro cytocompatibility and antibacterial effect were comparatively studied. After cold-drawing, the mechanical property, especially the elongation of the ф0.3 mm pure Zn wire was improved significantly compared with the ф3.0 mm pure Zn wire. The in vitro corrosion study including immersion and electrochemical test showed acceptable corrosion resistance of these two materials in Hank's solution. The in vitro Human Umbilical Vein Endothelial Cells (HUVECs) viability assay showed obviously different results, in which the ф0.3 mm pure Zn wire demonstrated favorable cytocompatibility, while the ф3.0 mm wire exhibited severe cytotoxic effect with 100% extract concentration. Both of them exhibited partly antibacterial effect on S. aureus. These results demonstrated the feasibility of the prepared 0.3 mm pure Zn wire as the potential suture material with good absorbability.